The influence of financial literacy and financial inclusion in student saving interest at bank BRI - Hilwa, Ta'batun; Fadilah, Siti; Al Mas, Nabila; Haryadi, Didit (Institute of Computer Science (IOCS), 2024)
The financial level of a country will encourage the development of the country's economy. Internal and external factors cause high and low financial management behavior. This study aims to develop a model that examines the three variables that the author has analyzed to determine the factors that can increase student interest in saving. This study used an associative descriptive quantitative method with a population of 102 respondents drawn into a sample using non-probability sampling, using saturated sampling / total sampling method. Data analysis techniques using linear regression with the help of SPSS software version 26. The first hypothesis of knowledge significantly affects students' interest in saving, the second hypothesis of financial literacy variables has a significant impact on students' interest in saving, and the third hypothesis of knowledge and financial literacy together can affect students' interest in saving. This research is expected to make theoretical contributions to the literature in this context, including in the context of financial and banking management.